2015
DOI: 10.1007/s13744-014-0263-4
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing the Total Mortality Caused by Two Species of Trichogramma on Its Natural Host Plutella xylostella (L.) at Different Temperatures

Abstract: Trichogramma pretiosum Riley and Trichogramma atopovirilia Oatman & Platner are natural enemies of Plutella xylostella (L.) in Southern Brazil. Laboratory studies to evaluate parasitoids performance under different conditions, such as temperature regimes, are necessary to assess their potential as biocontrol agents of P. xylostella. In most studies involving Trichogramma, parasitism rate is the main parameter used to evaluate parasitoid performance, ignoring that parasitoids can cause egg mortality by feeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Foerster et al (2014) obtained a higher percentage of parasitism of T. pretiosum and T. atopovirilia on eggs of Anticarsia gemmatalis (Hübner, 1818) (Lepidoptera: Noctuidae) at the temperature of 26°C. Marchioro et al (2015) observed the highest T. pretiosum and T. atopovirilia parasitism rates on eggs of Plutella xylostella (Linnaeus, 1758) (Lepidoptera: Plutellidae), at the temperatures of 20 and 25°C. In extreme temperatures, the low occurrence of parasitism may be associated with a reduction in the turgor of H. armigera eggs, which makes it difficult to insert the oviduct of the parasitoid into the host chorion, compromising its efficiency in the field.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Foerster et al (2014) obtained a higher percentage of parasitism of T. pretiosum and T. atopovirilia on eggs of Anticarsia gemmatalis (Hübner, 1818) (Lepidoptera: Noctuidae) at the temperature of 26°C. Marchioro et al (2015) observed the highest T. pretiosum and T. atopovirilia parasitism rates on eggs of Plutella xylostella (Linnaeus, 1758) (Lepidoptera: Plutellidae), at the temperatures of 20 and 25°C. In extreme temperatures, the low occurrence of parasitism may be associated with a reduction in the turgor of H. armigera eggs, which makes it difficult to insert the oviduct of the parasitoid into the host chorion, compromising its efficiency in the field.…”
Section: Resultsmentioning
confidence: 98%
“…depends on factors such as the knowledge of the species potential and/or strain to be employed, the host to be controlled, the thermal requirements and the influence of the prevailing weather conditions; thus, these factors may be decisive for the success of releases in the field (Marchioro et al, 2015;Coelho Jr. et al, 2016). The study of thermal requirements facilitates the understanding of the relationship between temperature and the biological control agent in addition to the prediction of the number of generations in the field (Reznik & Voinovich, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The use of Trichogramma wasps has been developed through extensive applied research ( Wang et al, 2014 ; Du et al, 2018 ; Hou et al, 2018 ; Wang et al, 2019b ; Gontijo et al, 2019 ; Guo et al, 2019 ; Wang et al, 2021 ; Zhang et al, 2021 ), their use being mostly through artificial inundative releases ( El-Arnaouty et al, 2014 ; Huang et al, 2020 ; Zang et al, 2021 ), although natural parasitism has been reported for possible conservation biological control ( Biondi et al, 2013 ; Bagheri et al, 2019 ; Salas Gervassio et al, 2019 ). They are used for biological control of many insect pests on various crops, e.g., vegetables and tree crops, and stored products ( Chailleux et al, 2013 ; Marchioro et al, 2015 ; Khan and Ruberson, 2017 ; Gontijo et al, 2019 ; Qu et al, 2020 ; Zang et al, 2021 ).…”
Section: Hymenopteramentioning
confidence: 99%